Port-Based Ontology Modeling for Robot Leg Conceptual Design. (10th December 2013) - Cao, Dongxing; Fu, Ming Wang; Mi, Jiajia; Li, Zhanwei
Abstract : Port, as an interface of the component, can be used to exchange information with its outer environment. It is the basis of the component concept and configuration generation. In this paper, port-based ontology representation is first given, and component knowledge and the primitive concepts are presented to describe robot leg ontological concepts. Secondly, the taxonomy of port-based ontology is built to map the component connections and interactions to cluster functional blocks, and their semantic synthesis is employed to describe component ontology. Next, an approach is proposed for computing semantic similarity by mapping terms to function ontology and by examining their relationships based on port ontology language. Furthermore, the construction process of port-based ontology concepts is described and its elements are related to the similarity between two concepts. Finally, a robot leg example is shown to illustrate the proposed approach.